2021
DOI: 10.47762/2020.964x.81
|View full text |Cite
|
Sign up to set email alerts
|

Nexus Between Smallholder Irrigation Farming and Farmers’ Livelihood Outcomes in Ghana’s Guinea Savannah

Abstract: The aim of the study was to relate small-scale irrigation farming and farmers’ livelihood outcomes using the poorest District in the Upper West Region of Ghana. The livelihood implications of rural farmers remain inconclusive across the literature. Mixed methods and primary data consisting of key informant interviews, household questionnaires and personal observation were used for the study. Data were obtained from 120 farmers drawn from 173 farming households living in four (4) small-scale irrigation dams’ co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The results showed that household headship in the CREMA communities is dominated by men ( Table 3 ) and reflects a dominant feature of household leadership in local communities in northern Ghana ( Baddianaah et al., 2020 ; Osumanu, 2020 ). With the household head being the main decision-making agent regarding the entire wellbeing of the household ( Osumanu, 2020 ), males have a greater chance of influencing decision-making regarding the CREMA management and exploitation of the resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that household headship in the CREMA communities is dominated by men ( Table 3 ) and reflects a dominant feature of household leadership in local communities in northern Ghana ( Baddianaah et al., 2020 ; Osumanu, 2020 ). With the household head being the main decision-making agent regarding the entire wellbeing of the household ( Osumanu, 2020 ), males have a greater chance of influencing decision-making regarding the CREMA management and exploitation of the resources.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study employed the simple random sampling technique by using the households' lists of each community and assisted by an excel tool pack, random numbers were generated for the households. Household heads were interviewed because of their high influence on decision-making at the household level and beyond ( Baddianaah et al., 2020 ; Osumanu, 2020 ). Thus, the household heads' responses regarding the management, challenges and benefits of the Zukpiri CREMA were solicited using a semi-structured questionnaire divided into three major sections.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies indicated that small-scale irrigation has improved crop production and enhanced overall rural livelihoods [ 26 , [40] , [41] , [42] ]. However, in these studies, there are a lot of generalizations.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, in recent years, the output from the agriculture sector continues to decline because of climate variability (high daily temperatures, erratic rainfall patterns), and the outbreak of pests and diseases. The communities mostly affected by the climatic change are rural communities in the northwestern part of Ghana whose dwellers are traditional food crop farmers (Mumin, 2017;Apuri et al, 2018;Baddianaah et al, 2020). It, therefore, stands to reason that local communities in this part of the country cannot solely rely on the agriculture sector for livelihood sustenance.…”
Section: Introductionmentioning
confidence: 99%
“…Household heads were chosen because they are the main decisionmakers within the household level. They stand the chance of influencing or determining the choice of livelihood strategy including financial decisions of the household (Osumanu, 2020;Baddianaah et al, 2020). Also, the snowball sampling technique was used in reaching out to three (3) leaders (bosses) of artisanal miners in each community (i.e.…”
mentioning
confidence: 99%